Selenium reduces oxaliplatin induced neuropathic pain: focus on TRPV1 - Çiğ, Bilal (Frontiers in Pharmacology, 2025)
Many drugs preferred for pain relief are insufficient against oxaliplatin (OX) induced neuropathic pain (OX-IN). Studies have shown that such pain mediators as the TRPV1 channel play a critical role in triggering high-sensitivity pain response in the dorsal root ganglia (DRG). TRPV1 activated by oxidative stress increases cytosolic free Ca2+ levels and leads to apoptotic cell damage. The key factors involved in the pathophysiology of OX-IN, which involves many components, are mitochondrial dysfunction and oxidative stress, both triggered by excessive Ca2+ influx across the neuronal membrane. Selenium (Se), an essential trace element, prevents the harmful effects of this oxidative stress through glutathione peroxidase. This study is based on understanding the neuroprotective role of Se, a cofactor for glutathione peroxidase, against TRPV1-mediated oxidative damage, mitochondrial dysfunction and apoptosis in OX-IN using molecular techniques such as patch clamp. The primary target in this study was DRGs as the initial station of OX-induced peripheral pain isolated in adult rats. In addition to the SN (sciatic) neurons isolated from the same animals, in vitro breast cancer cell (MCF-7) was also used to confirm the results. The study was conducted with four groups: control (5% dextrose), OX (4 mg/kg OX twice a week), Se (1.5 mg/kg Se every other day) and finally OX + Se, all of which were administered to the animals intraperitoneally for 4 weeks. The OX (50 μM for 24 h) and Se (200 nM for 2 h) were applied to MCF-7 cells in vitro. Although an excessive increase was observed in Tumour necrosis factor α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), as well as mitochondrial oxidative stress, apoptosis and TRPV1 channel overactivations in DRG and SN neurons under OX treatment, Se suppressed these negative effects. While OX reduced glutathione peroxidase and significantly increased malondialdehyde level (LP) in DRG neurons, Se reversed this situation. In conclusion, the TRPV1-mediated efficacy of Se in suppressing OX-induced pain symptoms was demonstrated and we concluded that Se should be considered in future therapeutic approaches in the treatment of OX-IN.